Intensity of exercise during road race pro-cycling competition - Fernandez-Garcia, B.; Terrados, N.; Perez-Landaluce, J.; Rodriguez-Alonso, M. (Medicine & Science in Sports & Exercise, 2000)
The aim of this study was to quantify the intensity of competition during two professional bicycle stage races: the Tour de France (Tour) and Vuelta a España (Vuelta). Methods: The HR responses of 18 world class cyclists were recorded during the races and compared with HR ranges that corresponded to four intensities of exercise that were measured in the laboratory with an incremental test to exhaustion 2 wk before each race. The four intensities were: Anaerobic (AN) over the individual anaerobic threshold, which was over 90% of V(dot)O2max; intense aerobic (IA), which was between 70 and 90% of V(dot)O2max; moderate aerobic (MA), which was between 50 and 70% of V(dot)O2max; and recovery (RE), which was < 50% of V(dot)O2max. The stages were divided in individual time trial (ITT), flat, or mountain. Results: The mean HR of the Vuelta and Tour were, respectively, 133.8 ± 17.9 and 134 ± 18.6 beats·min-1. The mean total time of each stage was 269.6 ± 122 and 259.4 ± 119.9 min. The mean stage time over IAT was 17.5 ± 15.7 and 24.7 ± 26 min; the IA time was 75.2 ± 47.6 and 79.6 ± 48.3 min; the MA was 97.2 ± 57.4 and 89.5 ± 54.9 min. Finally the RE time was 79.6 ± 60.5 and 65.4 ± 69.7 min. The percentage of participation related to total time of the race was, respectively, in the Vuelta and the Tour, 12.99 and 16.8% in AN exercise intensity, 29.5 and 29.2% in IA, 32.4 and 31.9% in MA, and 25.1 and 25.2% in RE. There are no differences in AN time among flat, mountain, and ITT stages in each race, except for the mountain stages in the Tour. Conclusion: Cycling is a high intensity sport because approximately 93 min in flat and 123 min in mountain stages were above 70% of V(dot)O2max. In addition, the time spent at IAT was roughly 20 min regardless of stage type, suggesting that the anaerobic capacity limits performance.